Exploring the Level of Mindfulness and Choking Under Pressure in Senior Taekwondo Athletes - Alodia Syahda Nadindra; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Background Problems: For senior taekwondo athletes, a problem that often arises is the phenomenon of choking under pressure, where competitive pressure causes athletes to fail to manage stress and experience sudden changes in concentration. This condition occurs mainly in athletes with low levels of awareness, meaning they cannot maintain focus and self-awareness in high-pressure situations. As a result, the maximum potential seen during training is not realized on the field, which hinders the achievement of optimal match results. Research Objectives: This study aims to explore the relationship between mindfulness levels and choking under pressure in senior taekwondo athletes. Methods: This study uses a quantitative descriptive method involving 25 senior taekwondo athletes from the Victory Bandung Taekwondo Club. The instruments used in the study were questionnaires consisting of MIS to measure mindfulness and SAS, SCS, and ACSI-28 to measure choking under pressure. Results: The results of the study showed that the level of mindfulness of senior taekwondo athletes reached 74.1% with the highest indicator in awareness (78.7%), followed by refocusing (75.2%) and non-judgmental (68.4%), while the level of choking under pressure reached 67.6% with the highest value in ACSI (71.4%), followed by SAS (65.6%) and SCS (64%). Conclusion: This study concludes that the higher the level of mindfulness in athletes, the lower the tendency for them to experience the phenomenon of choking under pressure. Coaches and athletes are advised to incorporate mindfulness training into their psychological training programs to improve mental resilience and manage stress effectively to maintain optimal performance in competitive situations.